Calcium/calmodulin-dependent protein kinase II couples wnt signaling with histone deacetylase 4 and mediates dishevelled-induced cardiomyopathy - Zhang, Min; Riffel, Johannes; Kreußer, Michael; Katus, Hugo; Backs, Johannes; Hardt, Stefan (Hypertension, 2015)
Activation of Wnt signaling results in maladaptive cardiac remodeling and cardiomyopathy. Recently, calcium/calmodulin-dependent protein kinase II (CaMKII) was reported to be a pivotal participant in myocardial remodeling. Because CaMKII was suggested as a downstream target of noncanonical Wnt signaling, we aimed to elucidate the role of CaMKII in dishevelled-1-induced cardiomyopathy and the mechanisms underlying its function. Dishevelled-1-induced cardiomyopathy was reversed by deletion of neither CaMKIIδ nor CaMKIIγ. Therefore, dishevelled-1-transgenic mice were crossed with CaMKIIδγ double-knockout mice. These mice displayed a normal cardiac phenotype without cardiac hypertrophy, fibrosis, apoptosis, or left ventricular dysfunction. Further mechanistic analyses unveiled that CaMKIIδγ couples noncanonical Wnt signaling to histone deacetylase 4 and myosin enhancer factor 2. Therefore, our findings indicate that the axis, consisting of dishevelled-1, CaMKII, histone deacetylase 4, and myosin enhancer factor 2, is an attractive therapeutic target for prevention of cardiac remodeling and its progression to left ventricular dysfunction.